2014
DOI: 10.2500/ar.2014.5.0090
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of the Flow Field in Realistic Nasal Septal Perforation Geometry

Abstract: The computational fluid dynamics (CFD) are used to evaluate the physiological function of the nose. We evaluated the aerodynamics of the nasal cavity in a patient with septal perforation (SP), pre- and postvirtual repair. Three-dimensional nasal models were reconstructed, and then a wide range of the pressure drops and flow rates were analyzed. The airflow velocity is higher in the central region and is lower around the boundary of the SP. The air velocity in the SP increases as the pressure drop increases. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…In line with the changes in pressure drop post RME, we observed a decrease in the velocity of air ow at the expiratory phase in group 2. This trend was supported by the results of Faramarzi et al, who evaluated the aerodynamics of the nasal cavity in a patient with septal perforation and found that velocity was higher in the area that showed a higher pressure drop [28]. In our study, we failed to observe any statistically signi cant change in terms of maximum wall shear stress between either T0 and T1 or the two groups.…”
Section: Cfd Simulationsupporting
confidence: 89%
“…In line with the changes in pressure drop post RME, we observed a decrease in the velocity of air ow at the expiratory phase in group 2. This trend was supported by the results of Faramarzi et al, who evaluated the aerodynamics of the nasal cavity in a patient with septal perforation and found that velocity was higher in the area that showed a higher pressure drop [28]. In our study, we failed to observe any statistically signi cant change in terms of maximum wall shear stress between either T0 and T1 or the two groups.…”
Section: Cfd Simulationsupporting
confidence: 89%
“…Computational fluid dynamics (CFD) has been used to analyze the characteristics of various nasal sinus conditions or procedures in efforts to better understand the associated effects on nasal airflow . However, there are relatively limited CFD data demonstrating the abnormal airflow patterns and the associated affects related to septal perforation in real patients; most prior published studies either use simulated perforations based on a healthy nose or have a sample size of 1 patient …”
mentioning
confidence: 99%
“…All as far as we are aware, they have looked only at the airflow inside the nasal cavity and not outside as in this study. Septum perforation was numerically assessed for pre-and post-operation condition 15 . Similar approach was also used by Nomura el al.…”
Section: Introductionmentioning
confidence: 99%